2012
DOI: 10.1111/j.1365-2036.2012.05072.x
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: the role of liver transplantation in the management of hepatocellular carcinoma

Abstract: SUMMARY BackgroundHepatocellular carcinoma (HCC) is a major cause of morbidity and mortality worldwide. Liver transplantation offers a potential cure for this otherwise devastating disease. The selection of the most appropriate candidates is paramount in an era of graft shortage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 128 publications
(253 reference statements)
0
36
0
1
Order By: Relevance
“…LT is a treatment for HCC, which was first performed in the late 80s and early 90s (45). Early studies indicated a poor outcome with regards to survival rates and high tumor recurrence (46,47).…”
Section: Periodontitis and Liver Diseasesmentioning
confidence: 99%
“…LT is a treatment for HCC, which was first performed in the late 80s and early 90s (45). Early studies indicated a poor outcome with regards to survival rates and high tumor recurrence (46,47).…”
Section: Periodontitis and Liver Diseasesmentioning
confidence: 99%
“…This concept of prophylactic LT for high-risk recurrent HCC before the development of recurrence is also called “de principe LT”[13]. Recently, some authors suggested the use of the histopathological features of the specimen of the resected tumor as the selection tool for LT to improve the outcome of cases with high recurrence rate after LR[13-16]. However, most of these histopathological features are also prognostic factors of post-transplant HCC recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Bridging therapy is thus needed to halt tumor progression and minimize wait list dropout [8,9]. Some patients with advanced HCC could benefit from OLT after downstaging the tumor with neoadjuvant treatment [10,11].…”
Section: Introductionmentioning
confidence: 99%